The Effect of Green Innovation on Firm Value at Different Life Cycle: The Role of Sustainable Growth and Debt Financing Cost - Wilutama, Nonie Anggun; Viverita, Viverita (Magister Akuntansi Universitas Pancasila, 2024)
Purpose: This study investigates the impact of green innovation on firm value at different stages of the life cycle of energy sector companies in Indonesia. It also examines the moderating effects of sustainable growth and debt financing costs. Methodology: The study utilizes panel data from 61 companies during the period from 2017 to 2022 to analyze the impact of green innovation on firm value and the moderating roles of sustainable growth and debt financing costs. Finding: The findings show that green innovation significantly increases firm value. However, the study finds that there is no significant moderating role of sustainable growth and debt financing costs on the impact of green innovation on firm value. Additionally, the influence of green innovation on firm value varies across life cycle stages. It positively affects firm value during the growth and decline stages, while the impact is not significant at the mature stage. Implication: These findings enhance our understanding of the importance of green innovation for improving the value of firms in the energy sector throughout their life cycles. Originality: This study provides a novel contribution by exploring the impact of green innovation on firm value in Indonesia's energy sector and assessing the moderating roles of sustainable growth and debt financing costs.